Altered Levels of Plasma Inflammatory Cytokines and White Matter Integrity in Bipolar Disorder Patients With Suicide Attempts - Jiang, Xiaowei; Guo, Yingrui; Jia, Linna; Zhu, Yue; Sun, Qikun; Kong, Lingtao; Wu, Feng; Tang, Yanqing (Frontiers in Psychiatry, 2022)
Objective: Bipolar disorder (BD) has a higher lifetime rate of suicide attempts (SA) than other psychiatric disorders. Furthermore, BD patients with SA (BD+S) are prone to a worse quality of life. However, the pathophysiology of BD+S is poorly understood. To further reveal the potential mechanisms of BD+S, abnormalities in peripheral plasma inflammatory cytokines and brain white matter (WM) in BD+S, as well as the correlation between them are investigated. Methods: We tested the levels of TNF-α, IL-1β, and IL-6 in peripheral plasma and collected the diffusion tensor imaging (DTI) data from 14 BD+S, 24 BD patients without SA (BD-S), and 26 healthy controls (HCs). The three groups were matched by age and gender. The levels of TNF-α, IL-1β, and IL-6 were detected by Luminex multifactor detection technology, and the fractional anisotropy (FA) values were employed to depict the alterations of WM. Partial correlation analyses were conducted to detect correlations between levels of TNF-α, IL-1β, and IL-6 and changes of WM, and the relationships between severity of clinical symptoms, including scores of HAMD-17 and YMRS, and cytokine levels or FA values in all groups. Results: For plasma inflammatory cytokines, there was no significant difference in their levels except for IL-6 among the three groups. Post-hoc analyses revealed that increased IL-6 level was only detected in BD+S (p<0.05, Bonferroni correction). For DTI, BD+S showed specifically decreased FA in the bilateral middle cerebellar peduncle and the left superior corona radiata compared to BD-S and HCs (p<0.05, Bonferroni correction). Additionally, both BD+S and BD-S groups revealed decreased FA in the bilateral body and genu of corpus callosum (CC) compared to HCs (p<0.05, Bonferroni correction). No significant correlation between plasma inflammatory cytokines and WM integrity was found. In the BD+S group, we found negative correlation between the scores of YMRS and FA values of the left middle cerebellar peduncle (r=-0.74, p=0.035). Conclusion: The inflammation and impaired WM integrity may provide a scientific basis to understand the potential mechanisms of BD+S.